Pengaruh Kredibilitas Karin Novilda sebagai Celebrity Influencer Produk Liquid Vape “CANDU terhadap Minat Beli Followers Instagram - Alam, Mutiara Nur; Yuliasari, Ika (LUGAS Jurnal Komunikasi, 2023)
Since the last few years, many business people have started to switch their market into digital and use technology to promote their products. They started to use social media influencers as a part of promotion. An influencer can be seen for their credibility from how high their followers buy interest.  Karin Novilda is a celebrity endorser on Instagram or commonly known as Awkarin. Currently, the number of Awkarin's followers is 7.9 million people. With the large number of her followers and current popularity, this is certainly considered very possible to influence her followers' buying interest in the "CANDU" liquid vape product. This study aims to know the effect and how much the effect of the credibility of Karin Novilda as a Celebrity Endorser of “CANDU liquid vape to her followers' buying interest. This study supports the theory of Source Credibility. This theory itself discusses that one's credibility has an important role in persuading the audience to determine their views. After using quantitative method research, it’s found that  Karin Novilda's credibility as a celebrity endorser has an influence of 27.6% on her followers' buying interest.